Auxin response factor 10 insensitive to miR160regulation induces apospory-like phenotypes in Arabidopsis - Pessino, Silvina Claudia (2024)
The Arabidopsis megaspore mother cell (MMC) arises from somatic cells in the ovule primordium and enters meiosis to generate four megaspores. Only the most chalazal (functional megaspore, FM) survives, undergoing a series of mitoses to form the female gametophyte. We show this commitment to the sexual germline requires spatial regulation of AUXIN RESPONSE FACTOR 10 (ARF10). GFP-fusion lines reveal ARF10 expression to be restricted to cells surrounding the MMC in wild type, but ectopically disseminated throughout the ovule in transgenic mARF10 lines insensitive to miR160, an ARF10 downregulator. Significantly, mARF10 ovules develop multiple FMs with differing ploidies, forming putative supernumerary gametophytes with altered polarity and cell identities – features of aposporous apomixis. Furthermore, we confirm the complexity of ovular ARF10 expression, being mediated by SEEDSTICK, ARGONAUTE1 and miR160. This work adds to our understanding of molecular switches possibly regulating aposporous apomixis, and may contribute the development of innovative plant breeding strategies.